If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + -10 = 30 + -2t Reorder the terms: -10 + 6t = 30 + -2t Solving -10 + 6t = 30 + -2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2t' to each side of the equation. -10 + 6t + 2t = 30 + -2t + 2t Combine like terms: 6t + 2t = 8t -10 + 8t = 30 + -2t + 2t Combine like terms: -2t + 2t = 0 -10 + 8t = 30 + 0 -10 + 8t = 30 Add '10' to each side of the equation. -10 + 10 + 8t = 30 + 10 Combine like terms: -10 + 10 = 0 0 + 8t = 30 + 10 8t = 30 + 10 Combine like terms: 30 + 10 = 40 8t = 40 Divide each side by '8'. t = 5 Simplifying t = 5
| -[8x-(3x+2)]=-5-[3(3x-4)-2x] | | V(x)=(11-2x)(17-2x)x | | -14p-4(3-5p)=4(p-5)-18 | | 0=5+10t+5t^2 | | Y=5-2.2x | | -26p-6(5-6p)=6(p-4)-30 | | 10x-7=5x+33 | | (2x^3/6y^4)^2 | | 4x^7-24x^6+16x^5= | | -26p-6(5-6p)=6(p-5)-30 | | 10x-7=5x+32 | | 5-1i= | | 10x-8=5x+33 | | y^5-y^8= | | 2/3x-5=1/2x-3 | | 9-(12/w)=-12 | | 2y/3y-1 | | -4(-5x+1)= | | 9-12/w=-12 | | (5/12x11/15) | | 6(n+2)+7=5n | | 3+4x+2-x=2 | | P=36-.05*25 | | 6x-9y=7 | | 20×2/3 | | 60-9s=51 | | 2/3×20 | | (4y^2-5y+8)-(9y^2-5y+5)= | | 24=6-3x | | mc=.02q | | -8x+8=8 | | 5x+-9=36 |